1990
DOI: 10.1029/rs025i005p01005
|View full text |Cite
|
Sign up to set email alerts
|

Gravity waves in the mesosphere observed with the middle and upper atmosphere radar

Abstract: We have observed wind motions from 60 to 90 km altitudes with the middle and upper atmosphere (MU) radar during daylight hours (0800-1600 LT) from October 13 to 31, 1986. Gravity waves with fairly sinusoidal vertical structure were evident on 16 days of the 19 days of observations. They were characterized by a typical vertical wavelength of 5-15 km and intrinsic periods centered at about 8.6 hours. The propagation velocity of these waves was determined using the linear gravity wave theory. All of the waves pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 40 publications
1
84
0
1
Order By: Relevance
“…Buhler et al (2003) studied the equatorward propagation of inertia gravity waves due to steady and intermittent wave forcing and showed that even wave sources outside the equatorial region can robustly produce potential energy spectra that peak at the equator. Tsuda et al (1990) found gravity wave motions of period centered around 8.6 h in the MU radar observations having equatorward component of the meridional propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Buhler et al (2003) studied the equatorward propagation of inertia gravity waves due to steady and intermittent wave forcing and showed that even wave sources outside the equatorial region can robustly produce potential energy spectra that peak at the equator. Tsuda et al (1990) found gravity wave motions of period centered around 8.6 h in the MU radar observations having equatorward component of the meridional propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Radar observations by Vincent and Fritts (1987) and rocket observations by Eckermann and Vincent (1989) in the Southern Hemisphere revealed some difference in the distribution of propagation directions between summer and winter. Tsuda et al (1990) found that the preferential direction of the dominant gravity wave component at 60-90 km altitude in October 1986 over Shigaraki Japan was south-southeastward. Gavrilov et al (1997) analyzed the internal gravity waves (IGWs) in the altitude range of 65-85 km over Shigaraki Japan by statistical methods; and decided that the propagation direction was mainly eastward in summer and westward in winter, they also decided that most of IGWs have momentum fluxes directed to the northeast in winter and to the east in summer.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the initial background is an isothermal atmosphere in hydrostatic equilibrium that is horizontally homogeneous; radar measurements (Tsuda et al, 1990) have shown that mean zonal winds in the range of 60±90 km altitude are 0±40 m s )1 , so the initial values of horizontal and vertical wind velocities in this study are assumed to be 10 and 0 m s )1 , respectively. Thus we have…”
Section: Initial Backgroundmentioning
confidence: 99%
“…However, any of the groundbased remote sensing facilities can only provide information of wave frequency and vertical wave number (Vincent and Fritts, 1987;Vincent 1994). The horizontal wave number is usually estimated by using the correlation analysis, or derived from the polarization and dispersion relations (Meek et al, 1985;Yamamoto et al, 1986;Manson, 1990;Tsuda et al, 1990). Therefore it is specially signi®cant to examine quantitatively the validity of dispersion and polarization relations based essentially on the linear gravity-wave theory in the nonlinear region.…”
Section: Introductionmentioning
confidence: 99%